The Braincase and Neurosensory Anatomy of an Early Jurassic Marine Crocodylomorph: Implications for Crocodylian Sinus Evolution and Sensory Transitions. Issue 11 (26th August 2016) - Brusatte, Stephen L.; Muir, Amy; Young, Mark T.; Walsh, Stig; Steel, Lorna; Witmer, Lawrence M.
ABSTRACT: Modern crocodylians are a morphologically conservative group, but extinct relatives (crocodylomorphs) experimented with a wide range of diets, behaviors, and body sizes. Among the most unusual of these fossil groups is the thalattosuchians, an assemblage of marine‐dwellers that transitioned from semiaquatic species (teleosaurids and kin) into purely open‐ocean forms (metriorhynchids) during the Jurassic and Cretaceous Periods (ca 191–125 million years ago). Thalattosuchians can give insight into the origin of modern crocodylian morphologies and how anatomy and behavior change during a major evolutionary transition into a new habitat. Little is known, however, about their brains, sensory systems, cranial sinuses, and vasculature. We here describe the endocranial anatomy of a well‐preserved specimen of the Jurassic semiaquatic teleosaurid Steneosaurus cf. gracilirostris using X‐ray micro‐CT. We find that this teleosaurid still had an ear well attuned to hear on land, but had developed large internal carotid and orbital arteries that likely supplied salt glands, previously thought to be present in only the fully pelagic metriorhynchids. There is no great gulf in endocranial anatomy between this teleosaurid and the metriorhynchids, and some of the features that later permitted metriorhynchids to invade the oceanic realm were apparently first developed in semiaquatic taxa. Compared to modern crocodylians, Steneosaurus cf. gracilirostris has a more limited set of pharyngotympanic sinuses, but it is unclear whether this relates to its aquatic habitat or represents the primitive condition of crocodylomorphs that was later elaborated. Anat Rec, 299:1511–1530, 2016. © 2016 Wiley Periodicals, Inc.